Studing the potential of complex sugars as new proteasome inhibitors - Berbel Menacho, Julia; Salas Pino, Silvia; Rodriguez Daga, Rafael; Díaz Moscoso, Alejandro (Biosaia: Revista de los másteres de Biotecnología Sanitaria y Biotecnología Ambiental, Industrial y Alimentaria, 2025)
The proteasome is the main cellular proteolytic complex responsible for degrading short-lived and damaged proteins. The proteasome is composed of a catalytic complex named 20S proteasome and a regulatory particle named 19S that provides substrate specificity. Proteasome function is critical for many different cellular processes such as cell-cycle regulation, apoptosis, immune response etc. (Adams 2003) and consequently proteasome dysfunction is associated to several human diseases such as cancer or neurodegenerative diseases. Furthermore, during aging, there is a progressive decline in the activity of the proteasome which contributes to the accumulation of protein aggregates resulting in loss of cell and tissue fitness (Hegde 2023). Thus, the search for proteasome modulators is one of the current challenges in cancer, aging, and neurodegeneration therapies. Several proteasome inhibitors such as Bortezomib or Carfilzomib…, are currently used for the treatment of certain types of cancer However, these inhibitors frequently lead to drug resistance, which highlight the necessity for a continuous search for new proteasome inhibitors (Nunes 2017). In this context, the main motivation of this work is the search for new structure-based proteasome inhibitors. Complex sugars are macrocyclic oligosaccharides with truncated cone geometry (Díaz-Moscoso 2010) which show structural similarity with the catalytic 20S proteasome. In this work, we are testing the effect of several complex sugars, specifically designed to match proteasome structure as potential inhibitors of the proteasome. By using live cell microscopy, cell fitness assays and a combination of in vivo and in vitro techniques to measure proteasome activity we show that several variants of these complex sugars have inhibitory activity on the proteasome in vitro and in vivo. In view of the results, we are currently characterizing the cellular effects of this complex sugars that have shown inhibitory activity on the proteasome and also, we are testing the effect on proteasome activity of new and improved variants of these complex sugars.